Vulnerability Assessment of Landscapes of the Kaliningrad Oblast for Environmental Management and Spatial Planning Optimization - Kesoretskikh, Ivan I.; Zotov, Sergey I. (International Journal of Economics and Financial Issues, 2015)
Regional applied research on comprehensive assessment of the territory for the purposes of optimization of environmental management and land use planning are now becoming increasingly popular among Russian researchers. The relevance of these studies is highlighted due to the necessity of introduction of environmentally oriented approaches to spatial planning system. This approach has found its application in the countries of Western Europe, where it takes place on legislative level, and in Russia it is not implemented fully. Aim of the study is to validate the methodology of integrated assessment of the Kaliningrad Oblast on the vulnerability of landscapes to anthropogenic influences. Result of the study is cartographic materials, which are the basis for the development of proposals for optimization of regional nature-use and existing scheme of spatial planning of the Kaliningrad Oblast. Keywords: Landscape, Vulnerability, Kaliningrad Region, Geographic Information Systems, regional Nature Management, Spatial Planning JEL Classifications: Q5, R1